Husband support, compliance in consuming Fe tablets and incident of anemia in pregnant women - Latifah; Rhamadayanti, Rizka Novia; Palimbo, Adriana; Fetriyah, Umi Hanik (Health Sciences International Journal, 2025)
Background: Anemia in pregnancy, particularly iron deficiency anemia, is a major public health concern with significant maternal and fetal implications. In Indonesia, anemia prevalence among pregnant women remains high, largely influenced by insufficient iron supplementation compliance and limited support systems. Husband support has been identified as a critical factor influencing maternal health behaviors, including compliance with consuming iron (Fe) tablets. Objective: This study aims to analyze the relationship between husband support, compliance in consuming Fe tablets, and the incidence of anemia among pregnant women. Method: A cross-sectional study was conducted involving 33 third-trimester pregnant women selected through purposive sampling. Data were collected using a validated questionnaire to assess husband support and maternal compliance with Fe tablet consumption. Hemoglobin levels were extracted from maternal health records. Statistical analysis included univariate and bivariate tests using the Fisher Exact Test and Chi-Square Test. Result: The study found significant relationships between husband support and anemia (p = 0.035) and between compliance with Fe tablet consumption and anemia (p < 0.001). Pregnant women with good husband support were less likely to experience anemia (6.1%) compared to those with poor support (18.2%). Similarly, none of the compliant participants developed anemia, while 24.2% of non-compliant women were anemic. Conclusion: Husband support and compliance with Fe tablet consumption are key factors in reducing anemia among pregnant women. Interventions should focus on enhancing spousal involvement and promoting adherence to iron supplementation to improve maternal and fetal health outcomes.